A 6-year-old boy with a focal lesion of the liver: case description - Sabina Baran; Katarzyna Ptak; Katarzyna Pawińska-Wąsikowska; Szymon Skoczeń; Walentyna Balwierz; Przemko Kwinta (Pediatria Polska)
Liver abscess is rare in the pediatric population, but it can be a challenge for physicians. The clinical symptoms of liver abscesses are nonspecific, which may lead to a delay in diagnosis and initiation of treatment. We present a case of a 6-year old boy with a hepatic abscess, probably resulting from inflammatory changes in the sinuses. Due to the unfavorable location, surgical intervention was abandoned. Complete regression of the lesion was observed following the implementation of conservative treatment. The article also presents a broad differential diagnosis of focal liver lesions, which can aid in establishing an accurate diagnosis in clinical practice.